The Impact of Service Quality and Delivery Time on Behavioral Intentions of E-Commerce Logistics Users with Customer Satisfaction as Mediation - Euis Saribanon; Anton Ferdiansyah; Jacinta Madalena Soares Lemos; Fikri Ferdiansyah Putra (Dinasti Review, 2025)
In the rapidly evolving digital age, e-commerce has emerged as one of the major forces in the global economic revolution. To remain competitive, e-commerce businesses must understand the components that influence the user behavior of their logistics services. Delivery time and service quality are two important factors that could affect customer satisfaction.Delivery time and service quality are two important factors that could affect customer satisfaction,which in turn causes them to be more likely to use this business again. Using customer satisfaction as a mediating factor, this study attempts to determine the effect of delivery speed and service quality on the intention of e-commerce consumers. This study uses a quantitative descriptive method and the Cochran formula to determine the number of samples used as many as 100 E-commerce user respondents. The data collection method in this study uses questionnaire. This study uses the Structural Equation Modeling-Partial Least Square (SEM-PLS) analysis technique. For this study systematic quantitative approaches in conjunction with random sampling techniques were used to gather data from e-commerce users. Based on the results of this study, Customer satisfaction has been shown to have a positive and large impact on delivery speed and service quality, as well as to positively and significantly influence behavioural intentions.